The Concise Encyclopedia of Statistics - Dodge, Yadolah (Springer New York : Imprint: Springer, 2008)
The Concise Encyclopedia of Statistics presents the essential information about statistical tests, concepts, and analytical methods in language that is accessible to practitioners and students of the vast community using statistics in medicine, engineering, physical science, life science, social science, and business/economics. The reference is alphabetically arranged to provide quick access to the fundamental tools of statistical methodology and biographies of famous statisticians. The more than 500 entries include definitions, history, mathematical details, limitations, examples, references, and further readings. All entries include cross-references as well as the key citations. The back matter includes a timeline of statistical inventions. This reference will be an enduring resource for locating convenient overviews about this essential field of study. Founder of the Master in Statistics program in 1989 for the University of Neuchâtel in Switzerland, Professor Yadolah Dodge earned his Master in Applied Statistics from the Utah State University in 1970 and his Ph.D. in Statistics with minor in Biometry from the Oregon State University in 1973. He has published numerous articles and authored, co-authored and edited several books including Mathematical Programming in Statistics (John Wiley 1981, Classic Edition 1993), Analysis of Experiments with Missing Data (John Wiley 1985), Alternative Methods of Regression (John Wiley 1993), Premier Pas en Statistique (Springer 1999), Adaptive Regression (2000), The Oxford Dictionary of Statistical Terms (2003), Statistique: Dictionnaire encyclopédique (Springer 2004), and Optimisation appliquée (Springer 2005). Professor Dodge is an elected member of the International Statistical Institute and a Fellow of the Royal Statistical Society.